The THE RELATIONSHIP OF ACADEMIC STRESS AND STRESS COOPING ON NURSING STUDENTS WHO ARE COMPLETING FINAL PROJECTS IN THE CONDITIONS OF THE COVID-19 PANDEMIC - Fathonah, Septiana (UPT PPM Sekolah Tinggi Ilmu Kesehatan Al Irsyad Al Islamiyyah Cilacap, 2021)
Notokusumo School of Health Sciences Yogyakarta is one of the best health education providers in Yogyakarta. One of the things that become excellence is in the process of education and teaching. The final project in the form of scientific writing is one of the subjects that must be taken by 6th semester students of the Diploma III Nursing Study Program at STIKES Notokusumo Yogyakarta. The current COVID-19 pandemic has an impact on students, including university students. Students must carry out learning using online methods, including in the preparation of the final project. Nursing students in particular are experiencing stress during the Covid-19 pandemic. Student stress levels tend to be influenced by the coping mechanisms used. Based on this, the researchers wanted to know the relationship between academic stress and coping stress on students who are compiling their final project in the current state of the COVID-19 pandemic. This research approach is quantitative research with correlation descriptive approach. Non-probability sampling with purposive sampling method. Based on the results of data analysis, the significance value of the Pearson Correlation Test between academic stress and coping stress was 0.052 <0.05 ( value). This shows that there is no significant correlation (relationship) between academic stress and coping stress in students who compose KTI during the current COVID-19 pandemic.